Neonatal seizure monitoring and representation - Poh, Kok Kiong (2013)
Approximately 1 — 3/1000 newborn babies in the US experience some form of seizure activities. These seizure activities, in general, indicate that some form of brain abnormalities are present in the babies. Prolonged seizures can result in brain damage or even death. Therefore, it is important to detect and control seizure activities promptly to avoid permanent cerebral damage.